Parallel techniques for speckle noise reduction in medical ultrasound images. (October 2020) - Arnal, Josep; Mayzel, Ilya
Highlights: Parallel computing reduces the computational time in despeckling process. Combination of filters improves speckle reduction in ultrasound imaging. Filters need parallelization to meet real-time requirements of ultrasound systems. Abstract: Parallel computing is used to accelerate the computations in the reduction of speckle noise in medical ultrasound images. A new hybrid algorithm for speckle noise reduction in medical ultrasound images is proposed and compared to an existing efficient method. The method combines in an efficient manner the advantages of several denoising filters using local and non-local information. A comparative study is carried out using quantitative and qualitative measures and showing the competitiveness of the proposed method. Both methods are parallelized using OpenMP, and a hybrid combination of MPI and OpenMP. The parallel implementations are compared to the sequential ones, obtaining significative values of speedup.